Międzynarodowa współpraca w zakresie bezpieczeństwa energetycznego w ramach ASEAN i APEC - Mazurek, Szymon (International energy security co-operation in ASEAN and APEC, 2009)
Energy security is an international issue. Addressing broader challenges in this area requires regional or even global co-operation. Both A SEAN and APEC are trying to ensure greater security and sustainability of energy supply through diversification, development and conservation of resources, the efficient u se of energy, and the wider application of environmentally sound technologies
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 190-198